Distributed Proxy Server dengan Squid pada Sistem Operasi Windows 7 - Gina Akmalia; Elvyna Tunggawan; Kevin Sungiardi; Alfian Lazuardi (Universitas Multimedia Nusantara, 2013)
Proxy server is the intermediary between client and the Internet. The usage of proxy server is one of many means to avoid excessive access to the Internet. Proxy server’s cache will save every web page which has been accessed, so clients can save their bandwidth when they access same web pages repeatedly. Distributed proxy is a collection of connected proxy servers which has shared cache. This research will prove that distributed proxy server can shorten data access time and minimize bandwidth. On this research, we use Squid Proxy Server on Windows 7 as the main tool. Index Terms - distributed proxy, shared cache, Squid